Discovering aspects of health—experiences of a web‐based health diary among adults with primary immunodeficiency. Issue 4 (10th July 2018) - Petersson, Christina; Björkander, Janne; Fust, Ramona
Abstract: Aim: Advances in technology generate new opportunities to develop e‐health tools to help individuals in self‐management by assessing symptoms of illness and its relation to treatments. Self‐management is central when living with primary immunodeficiency diseases. The aim was to explore the experiences of people living with primary immunodeficiency, who used a pilot version of the web‐based health diary. Design: Explorative design. Methods: In total, 16 participants (median age 59) attended one of three focus groups. Inductive content analysis was used. Results: The participants could be encouraged to discover aspects of their health by contributing to documentation which could support the health concept. A greater understanding about their own health and communicating with healthcare professionals during encounters was expressed. The web‐based health diary is a helpful tool to discover aspects of health that affects the individuals' life situation and assists the self‐management of a long‐term condition such as immunodeficiency.